Public Private Partnership in Coal Mining Model Concession Agreement - Planning Commission (Planning Commission, 2014)
Coal accounts for over 50 per cent of country’s primary source of commercial energy supply and is critical for meeting the rising energy demand in the country. However, the gap between demand and domestic supply has widened in the recent years, thereby increasing the dependence on imported coal for meeting the energy demand. The share of imports in the total coal supply in India is estimated to have increased from 10 per cent in 2006-07 to about 28 per cent in 2012-13. In view of the high price of imported coal, it is imperative to augment domestic coal production both from the public sector, and the private sector and to expedite the reform process for realising efficiency gains through increased competition in the sector during the Twelfth Plan.
Planning Commission Government of India
Planning Commission Government of India